2015
DOI: 10.1080/08964289.2014.965127
|View full text |Cite
|
Sign up to set email alerts
|

Video Gaming Disorder and Sport and Exercise in Emerging Adulthood: A Longitudinal Study

Abstract: Among the negative consequences of video gaming disorder, decreased participation in sport and exercise has received little attention. This study aimed to assess the longitudinal association between video gaming disorder and the level of sport and exercise in emerging adult men. A questionnaire was completed at baseline and 15-month follow-up by a representative national sample of 4,933 respondents. The seven items of the Game Addiction Scale were used to construct a latent variable representing video gaming d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 38 publications
3
37
0
5
Order By: Relevance
“…Sin embargo, las puntuaciones en estas categorías aumentaban significativamente para el nivel de uso medio. Henchoz et al (2016), en un estudio longitudinal, determinan relaciones de causalidad entre trastornos relacionados con el uso de videojuegos y menores niveles de ejercicio físico, lo que justifica las menores puntuaciones obtenidas en el Clima Ego en este estudio cuando el nivel de uso es elevado. Por otro lado, los individuos que poseen un nivel medio de atracción hacia videojuegos (sin ser patológico), no ven damnificados sus hábitos físicos saludables significativamente (Chacón Cuberos et al, 2015;Staiano;Abraham;Calvert, 2013), pudiendo mostrar mayores niveles de Clima Ego que son propiciados por el componente competitivo del videojuego (Van Rooij et al, 2011;Ventura;Shute;.…”
Section: Discussionunclassified
“…Sin embargo, las puntuaciones en estas categorías aumentaban significativamente para el nivel de uso medio. Henchoz et al (2016), en un estudio longitudinal, determinan relaciones de causalidad entre trastornos relacionados con el uso de videojuegos y menores niveles de ejercicio físico, lo que justifica las menores puntuaciones obtenidas en el Clima Ego en este estudio cuando el nivel de uso es elevado. Por otro lado, los individuos que poseen un nivel medio de atracción hacia videojuegos (sin ser patológico), no ven damnificados sus hábitos físicos saludables significativamente (Chacón Cuberos et al, 2015;Staiano;Abraham;Calvert, 2013), pudiendo mostrar mayores niveles de Clima Ego que son propiciados por el componente competitivo del videojuego (Van Rooij et al, 2011;Ventura;Shute;.…”
Section: Discussionunclassified
“…Article first published online: December 1, 2017 in the Journal of Health Psychology, Post-print Version https://doi.org/10.1177/1359105317740414 a lack of physical activity (Henchoz et al, 2016;Rehbein et al, 2010) even though this relationship is not causal (Mentzoni et al, 2011). This assumption is plausible given that videogames can jeopardise engagement in physical activities leading to sedentary behaviour (Rideout et al, 2010).…”
Section: Article Informationmentioning
confidence: 97%
“…Accordingly, PGB was found to be associated with experiences of physiological symptoms such as somatisation (Kim et al, 2016b;Müller et al, 2015;Starcevic et al, 2011), shifts in the autonomic nervous system (Coyne et al, 2015) and plasma catecholamine responses (Kim et al, 2016a). Additionally, PGB was found to be associated with decreased levels of physical activity (Henchoz et al, 2016;Montag et al, 2011) and hand and wrist pain (Gentile, 2009). A recent study (Kim and Kim, 2015) found that PGB induced cardiovascular stress reaction in gamers, leading to a decrease in plasma catecholamine norepinephrine (NE) and epinephrine (Epi) levels over time.…”
Section: Article Informationmentioning
confidence: 99%
“…Problematic Internet and gaming use furthermore appears highly comorbid with various other mental and physical disorders, including depression, anxiety disorders, obesity, and attention-deficit hyperactivity disorder (Henchoz et al., 2016; Pontes & Griffiths, 2016; Turel, Romashkin, & Morrison, 2016; Yen et al., 2016), and psychological and psychopharmacological treatments used for these disorders appear similarly efficacious in treating Internet addiction and gaming addiction (Kuss & Lopez-Fernandez, 2016), putting into question the ability to differentiate mental disorder diagnoses (King & Delfabbro, 2013). This exacerbates everyday diagnostic practice in both clinical as well as research contexts.…”
Section: Igd Diagnosis: Issues and Concernsmentioning
confidence: 99%